1996
DOI: 10.1021/jm960228q
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of HIV Protease Inhibitors:  5,6-Dihydro-4-hydroxy-2-pyrones as Effective, Nonpeptidic Inhibitors

Abstract: From a broad screening program, the 4-hydroxycoumarin phenprocoumon (I) was previously identified as a lead template with HIV protease inhibitory activity. The crystal structure of phenprocoumon/HIV protease complex initiated a structure-based design effort that initially identified the 4-hydroxy-2-pyrone U-96988 (II) as a first-generation clinical candidate for the potential treatment of HIV infection. Based upon the crystal structure of the 4-hydroxy-2-pyrone III/HIV protease complex, a series of analogues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…37 Most notably, the use of crystallographic overlays of the evolving nonpeptidic inhibitors with potent peptidomimetic compounds was critical to the expeditious drug design process. In the coumarin/pyrone series, inspection of the crystallographic overlays 34 suggested that the meta position on the C-3␣ phenyl ring of the coumarin lead was in close proximity to the C-␣ position of the histidine residue of peptidomimetic inhibitor 2 ( Figure 4).…”
Section: Structure-based Discovery Of Pnu-140690ementioning
confidence: 99%
See 2 more Smart Citations
“…37 Most notably, the use of crystallographic overlays of the evolving nonpeptidic inhibitors with potent peptidomimetic compounds was critical to the expeditious drug design process. In the coumarin/pyrone series, inspection of the crystallographic overlays 34 suggested that the meta position on the C-3␣ phenyl ring of the coumarin lead was in close proximity to the C-␣ position of the histidine residue of peptidomimetic inhibitor 2 ( Figure 4).…”
Section: Structure-based Discovery Of Pnu-140690ementioning
confidence: 99%
“…Initial studies 37 were directed toward the 5,6-dihydropyrone template and mirrored efforts being advanced on the pyrone nucleus. Separate studies 42,43 in other labs have also focused on this ring system.…”
Section: Structure-based Discovery Of Pnu-140690ementioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that microbial 2-pyrones, dihydro-2-pyrones, and secondary metabolites exhibit a wide range of antifungal, cytotoxic, neurotoxic, and phytotoxic properties (Dickinson, 1993). These compounds also display antitumor and HIV-inhibitory activities (Thaisrivongs et al, 1996;Poppe et al, 1997;Turner et al, 1998), which reinforces their potential medicinal importance. In addition, an investigation of the anticancer properties of tricyclic 2-pyrones showed that these compounds prevented DNA synthesis and growth in human leukemic cells in vitro (Trachootham et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The importance of similar pyrones as potential fungicides is reinforced by the existence of several natural fungicides possessing structures analogous to 5, 6-dihydro dehydroacetic acid, like alternaric acid, the podoblastins and lachnelluloic acid [3][4][5], studies have shown that such compounds and their complexes have very interesting biological properties [6][7][8][9][10][11][12][13]. Like dehydroacetic acid, mercaptotriazoles and their complexes have been shown to posses enhanced biological activities [14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%